An often neglected area in crooked nose: middle turbinate pneumatization - Özdoğan,Fatih (2017)
Abstract Introduction: Crooked or deviated nose is a deviation of the nose from the straight vertical position of the face. Extensive pneumatization of the middle turbinate, also called concha bullosa or bullous middle turbinate (BMT) is known to be one of the possible etiologic factors in nasal obstruction, recurrent sinusitis, and headache. There is no study concerning a link between BMT and crooked nose. Objective: To investigate the association between crooked nose and the presence of a BMT. Methods: A total of 199 patients who underwent open septorhinoplasty were retrospectively analyzed. Preoperative paranasal Computerized Tomography (CT) findings, preoperative photodocumentation, and anterior rhinoscopic examination findings were documented. Of the 199 patients, 169 were found to meet the criteria and were included in the study. CT scans were examined to note the presence of BMT, inferior turbinate hypertrophy, and septum deviation (SD). SDs and crooked noses were classified. Results: Ninety-four of 169 patients (56%) presented a crooked nose deformity and seventy-five of 169 patients (44%) presented a straight nose. While 49 (52%) crooked nose patients had a bulbous and extensive BMT, 20 patients with straight nose (26.6%) had a BMT. A statistically significant relationship was found between the presence of crooked nose and BMT, regardless of the side of the disease (p = 0.011). Conclusion: This study revealed a link between crooked nose and BMT.